Diagnostic Accuracy of Five Different Fecal Markers for the Detection of Precancerous and Cancerous Lesions of the Colorectum - Mariann Rutka; Renáta Bor; Anita Bálint; Anna Fábián; Ágnes Milassin; Ferenc Nagy; Zoltán Szepes; Mónika Szűcs; László Tiszlavicz; Klaudia Farkas; Tamás Molnár (Hindawi Limited, 2016)
Background. Colorectal cancer (CRC) is the second deadliest malignancy worldwide. This study aimed to compare the diagnostic accuracy of different fecal markers in the detection of colorectal adenomas and cancer. Methods. Stool samples of patients referred to colonoscopy were collected for the analysis of tumor M2 pyruvate kinase (M2PK), human hemoglobin (Hb), hemoglobin/haptoglobin (Hb/Hp) complex, fecal calprotectin (FC), and matrix metalloproteinase-9 (MMP-9). Results. Sensitivity and specificity of M2PK for adenomas sized > 1 cm were 60% and 67.5% and for CRC were 94.7% and 67.5%. Sensitivity and specificity of iFOBT for adenomas sized ≥ 1 cm were 80% and 72.5% and for CRC were 94.7% and 72.5%. Sensitivity and specificity of Hb/Hp complex for adenomas sized ≥ 1 cm were 80% and 52.9% and for CRC were 100% and 52.9%. Sensitivity of FC and MMP-9 for CRC was 77.8% and 72.2%. Combined use of M2PK, iFOBT, and FC resulted in a sensitivity and specificity of 95% and 47.5% for the detection of adenomas sized ≥ 1 cm. Discussion. In CRC, sensitivity of M2PK, iFOBT, and Hb/Hp complex proved to be high. Combined use of M2PK, iFOBT, and FC may be valuable in the detection of large adenomas.